Electromyographic evaluation of masseter and anterior temporalis muscles in resting position and during maximum tooth clenching of edentulous patients before and after new complete dentures. - Goiato, Marcelo Coelho [UNESP]; Garcia, Alício Rosalino; Santos, Daniela Micheline dos [UNESP] (My University, 2007)
The aim of this study was to assess the electrical activity of the masseter and anterior temporal muscles in patients with severe bone resorption, with complete dentures worn for over ten years, and five months after having new dentures put in place. The RDC questionnaire was applied to twelve asymptomatic patients, before and five months after new dentures were put in place. The electrical activity recordings were made in the mandibular position at rest, and during maximum tooth clenching. The electrical activity of the masseter and anterior temporal muscles in the position at rest presented no statistically significant difference after five months of wearing the new complete dentures. Electrical activity during tooth clenching exhibited a statistically significant reduction only in the right temporal muscle. A period longer than five months of wearing the new complete dentures is required for adaptation and the acquisition of functional capacity.
Keywords: adaptation; aged; denture; electromyography; female; follow up; human; jaw disease; longitudinal study; male; masseter muscle; middle aged; mouth disease; muscle contraction; osteolysis; pathophysiology; physiology; temporalis muscle; tooth occlusion; Adaptation, Physiological; Aged; Aged, 80 and over; Bone Resorption; Denture, Complete; Denture, Complete, Lower; Denture, Complete, Upper; Electromyography; Female; Follow-Up Studies; Humans; Jaw Diseases; Longitudinal Studies; Male; Masseter Muscle; Middle Aged; Mouth, Edentulous; Muscle Contraction; Temporal Muscle; Vertical Dimension